SEASONAL LIFE HISTORY PLASTICITY OF THE GROUP OF WINTER WHEAT AND TRITICALE ACCESSIONS - V. E. Kozlov; V. I. Ponomarenko; E. P. Razmakhnin (Вавиловский журнал генетики и селекции)
The application of “spring analogs” to explore winterhardiness of wheat gives the possibility to obtain cultivars with higher hardiness. Seasonal life history plasticity of winter cultivars gives the possibility to obtain such “analogs”. Winterhardiness of 34 winter wheat and triticale accessions from Krasnodar was tested in West Siberia environment. Their ofsprings were sown early in the spring near Novosibirsk to study their plasticity and to obtain “spring analogs”. In the fall the percentage of fertile plants was equal to 0 in the case of 5 accessions and to not more than 59.3 in other 29 accessions partly because of the  presence of sterile plants. The progeny of this sowing was sown next year late in the spring. As a result, in the fall fer tile plants were observed in the progeny of only 15 winter accessions. Also plants at the stage of tillering were observed in the progeny of 28 accessions at the beginning of winter. Some of them survived and developed seeds next year earlier than winter cultivars. Variability in performance was observed between these plants in spite of sandy soil (low humidity content) and May-June strong drought. So, such “winter-spring” plants can be used for breeding wheat and triticale accessions suitable for sowing late in the spring or early in the summer and harvesting next year earlier than winter cultivars. They can be developed in accordance with sustainable agriculture, because “winter-spring” plants were generated in an extremely unfavourable environment: sandy acid soil (pH 4.9–5.3) with low fertility (nitrogen content in the upper 40-cm layer was below 25 kg/ha) without fertilizer application. There is a theoretical posibility to breed “winter-spring” plants in simultaneous sowings with spring cultivars.